Nitric oxide photo-release from a ruthenium nitrosyl complex with a 4, 4′-bisfluorenyl-2, 2′-bipyridine ligand. (1st September 2018) - Roose, Max; Sasaki, Isabelle; Bukhanko, Valerii; Mallet-Ladeira, Sonia; Barba-Barba, Rodrigo M.; Ramos-Ortiz, Gabriel; Enriquez-Cabrera, Alejandro; Farfán, Norberto; Lacroix, Pascal G.; Malfant, Isabelle
Graphical abstract: A ruthenium (II) complex with two fluorene fragments can release nitrosyl oxide under irradiation at 400 nm. The release can be achieved in the therapeutic window by two-photon irradiation at 800 nm, with a cross section of 156 ± 23 GM. Abstract: A ruthenium nitrosyl complex of formula [Ru II (terpy)(F2B)(NO)](PF6 )3, where terpy stands for 2, 2′:6′, 2″-terpyridine and F2B for 4, 4′-bis(9, 9′-dibutyl-9H-fluoren-2-yl)-2, 2′-bipyridine, is presented and fully characterized. The X-ray crystal structure of F2B is reported. The electronic properties of the complex are compared to those of related [Ru II (terpy)(bpy)(NO)] 3+ complexes having a bipyridine (bpy) free of fluorene or bearing a fluorene on the terpyridine ligand. DFT computations are provided to support the experimental data. [Ru II (terpy)(F2B)(NO)](PF6 )3 releases NO under irradiation at 405 nm with a quantum yield ( ϕ NO ) equal to 0.033. Additionally, the two-photon absorption cross-section investigated at 800 nm by the Z-scan technics is equal to 156 ± 23 GM, which indicates that the complex can release NO under irradiation in the therapeutic window.